Assessing environmental impacts of major vegetable crop production systems of East Azerbaijan province in Iran. Issue 7 (7th June 2018) - Mohammadzadeh, Arash; Vafabakhsh, Javad; Mahdavi Damghani, Abdolmajid; Deihimfard, Reza
ABSTRACT: In the present study, environmental effects of carrot, tomato, potato and onion production systems were evaluated using the quantitative indices of energy efficiency, global warming potential (GWP), economic indicators, pesticide risk (field environmental impact quotient – FEIQ), tillage impact (TI), fertilizer, land and water use efficiency, and the eco-efficiency index (ratio of gross production to environmental impact for GWP, FEIQ and TI). Data was collected from 110 farmers by survey to determine crop production in the region. The results showed that the energy index for the potato production system was the most efficient; however, the carrot production system was the best in terms of the economic and environmental indices of GWP, FEIQ and TI. For irrigation water productivity (IWP) and land production efficiency (LPE), the potato production system was superior. The carrot production system had the highest values for economic irrigation water productivity (EIWP), economic land production efficiency (ELPE) and phosphorous and potassium use efficiency. The tomato production system recorded the lowest nitrogen use and highest nitrogen use efficiency. It can be concluded that the onion production system was furthest from sustainability goals based on the aforesaid indices.